Simulation Aspects of the High Pressure Die Casting Process - Bubenkó, Marianna; Molnár, Dániel (International Journal of Engineering and Management Sciences, 2019)
High pressure die casting (HPDC) is a manufacturing process for producing accurately dimensioned, sharply defined, smooth or textured surface metal parts. It is accomplished by injecting liquid metal at fast velocity and under high pressure into reusable steel dies. Compared to other casting processes, die casting is at the top end of both velocity and pressure. The high velocity translates into a very turbulent flow condition. The process is often described as the shortest distance between raw material and the finished product.